U–Pb SHRIMP detrital zircon ages from the Neoproterozoic Difunta Correa Metasedimentary Sequence (Western Sierras Pampeanas, Argentina): Provenance and paleogeographic implications - Ramacciotti, Carlos Dino (2015)
The central and eastern parts of the Sierra de Pie de Palo (Western Sierras Pampeanas, Argentina) areformed by a Mesoproterozoic basement and a Neoproterozoic sedimentary cover. Both were involvedin an accretionary orogeny (penetrative deformation and metamorphism) along the southwestern mar-gin of Gondwana in the Ordovician (i.e., Famatinian Orogeny). New U?Pb SHRIMP detrital zircon agesfrom the Neoproterozoic Difunta Correa Metasedimentary Sequence (DCMS), record the characteristicsof this region at the time of sedimentation. Detrital zircon ages range from Neoarchean to Neoprotero-zoic, with main peaks at ca. 1.0-1.3 Ga and ca. 1.35-1.5 Ga. Geological and geochronological evidencesfrom the DCMS suggest that the sediments were derived from both, the Grenville province and theGranite-Rhyolite province in the southeastern side of present Laurentia, and from the nearby Grenville-age basement of Western Sierras Pampeanas. This latter basement has been interpreted as the resultof the accretion and reworking of the South American Paleoproterozoic MARA craton to southeasternLaurentia during the Grenvillian Orogeny, which remained juxtaposed throughout the Neoproterozoic.The detrital zircon patterns of the DCMS support the hypothesis that this sequence was deposited in thePuncoviscana/Clymene Ocean during the Ediacaran at the southeastern passive margin of MARA. Thiscraton eventually broke away from Laurentia in the late Neoproterozoic-early Paleozoic, which led to theopening of the Iapetus Ocean. MARA drifted along the Proto-Pacific Ocean, and finally collided againstthe southwest Gondwana margin during the Cambrian (i.e., Pampean Orogeny).